1984
DOI: 10.1021/bi00308a036
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the individual collagenases from Clostridium histolyticum

Abstract: The six collagenases (alpha, beta, gamma, delta, epsilon, and zeta) from Clostridium histolyticum isolated in the preceding paper [Bond, M. D., & Van Wart, H. E. (1984) Biochemistry (first paper of three in this issue)] have been characterized in detail. The molecular weights determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis range from 68 000 to 125 000. Isoelectric focusing experiments demonstrate that the isoelectric points of the collagenases are in the 5.35-6.20 range. These experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
1
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(153 citation statements)
references
References 29 publications
10
141
1
1
Order By: Relevance
“…Binding of ColH was not inhibited by low temperature unlike activity, suggesting that binding is independent of hydrolysis. In a commercial preparation of C. histolyticum collagenase, Bond and Van Wart (22)(23)(24) reported the presence of multiple forms of collagenases which showed similar peptide maps and amino acid analyses. They suggested that this organism harbors multiple collagenase genes (4).…”
Section: Discussionmentioning
confidence: 96%
“…Binding of ColH was not inhibited by low temperature unlike activity, suggesting that binding is independent of hydrolysis. In a commercial preparation of C. histolyticum collagenase, Bond and Van Wart (22)(23)(24) reported the presence of multiple forms of collagenases which showed similar peptide maps and amino acid analyses. They suggested that this organism harbors multiple collagenase genes (4).…”
Section: Discussionmentioning
confidence: 96%
“…Harper et al (1965) isolated two collagenases from Clostridium histolyticum with molecular weights of 105 and 57 kDa. Bond and Van Wart (1984) isolated six different collagenases from the same species with molecular weights ranging from 68-128 kDa. Matsushita et al (1994) reported that collagenases isolated from a related species of Clostridium perfringens had molecular weights ranging from 80-120 kDa.…”
Section: Collagenase and Collagenolytic Enzymesmentioning
confidence: 99%
“…Bond and Van Wart (1984) suggested that some of the variation in reported molecular weights of collagenases may be simply due to proteolysis of a larger collagenase precursor. For use in industry, such variation will be less important than overall collagenolytic activity but the potential for variation should be noted.…”
Section: Collagenase and Collagenolytic Enzymesmentioning
confidence: 99%
“…Thus, synergistic cleavage of collagen fibers suggested for different fractions (16,33) is as yet uncertain. Even the question of whether all the isozymes arise from cleavage of a single progenitor molecule or if some are coded by similar but different genes (5,7) remains to be answered.…”
mentioning
confidence: 99%